1, 3 Dioxolane versus tetrahydrofuran as promoters for CO2-hydrate formation: Thermodynamics properties, and kinetics in presence of sodium dodecyl sulfate. (14th April 2015) - Torré, J.-P.; Haillot, D.; Rigal, S.; de Souza Lima, Roger; C., Dicharry; J.-P., Bedecarrats
Abstract: This paper makes a comparison between tetrahydrofuran (THF) and 1, 3 dioxolane (DIOX) in terms of their respective performances as promoters for the formation of clathrate hydrates with CO2 . The aim is to find products that can be substituted for THF, which is known to be harmful and difficult to handle. Drawing on a review of the chemical and physical properties of these two organic compounds, experiments were performed using high-pressure differential scanning calorimetry (DSC) and a batch reactor. Details of the thermodynamic equilibria of mixed THF+CO2 and DIOX+CO2 hydrates obtained with various additive concentrations are provided, along with hydrate kinetics data relating to the hydrate formation. The effect of the presence of an anionic surfactant, SDS (sodium dodecyl sulfate), on hydrate formation kinetics was also evaluated, showing that a combination of THF or DIOX and SDS is a very advantageous solution for accelerating hydrate formation. THF has been found to outperform DIOX as a hydrate promoter from both a thermodynamic, and a kinetic standpoint in presence of SDS. However, DIOX remains an interesting practical solution, due to the benefits offered as the least toxic and aggressive of these two organic compounds. Graphical abstract: Highlights: Search for efficient and easy-to-use promoters for clathrate hydrate formation. Experimental results obtained by using high-pressure calorimetry and a batch reactor. Data on hydrate phase equilibrium and kinetics obtained using DIOX, THF, and SDS. The combination of THF or DIOX with SDS speeds up enclathration. THF, used alone or with SDS, is a more effective hydrate promoter than DIOX.